Witold Bosonóg, czyli polska [nie]dojrzała (nie)dojrzałość. Casus strukturacji tożsamości - Chojnacki, Marek (Tematy i Konteksty, 2017)
Due to surprisingly different historical testimonies about Polish identity and character – Poles being astonishingly kind-hearted, naive and polite and at the same time quarrelsome and incapable of acting together – how should a peculiar weakness of Polish social existence leading to „ritual chaos” be understood? Gombrowicz in his ironic historical dramas – in Ślub (Wedding), in Historia (History), in Operetka (Operetta) – leads us to discovering mature immaturity understood much more widely than just criticism of Polish form or „trap” suggesting the possibility of critical but conscious accepting Polishness as a feeling of helplessness in the face of this world powers, a weak, unfinished and vague identity and at the same time showing unexpected benefit from this seemingly hopeless situation: Polish weakness, self-conscious, unassertive identity gives a chance to react more flexibly, maturely to revolutionary changes in contemporary world. Speaking the language of contemporary subjective sociology the Habermas vision of ideal community of communication is defeated by Anthony Giddens’s description of structuration in which true mechanisms of creating efficient collective identities can be seen.